5(x+3)=(3+2)x(x+(2+1))

Simple and best practice solution for 5(x+3)=(3+2)x(x+(2+1)) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x+3)=(3+2)x(x+(2+1)) equation:



5(x+3)=(3+2)x(x+(2+1))
We move all terms to the left:
5(x+3)-((3+2)x(x+(2+1)))=0
We add all the numbers together, and all the variables
5(x+3)-(5x(x+3))=0
We multiply parentheses
5x-(5x(x+3))+15=0
We calculate terms in parentheses: -(5x(x+3)), so:
5x(x+3)
We multiply parentheses
5x^2+15x
Back to the equation:
-(5x^2+15x)
We get rid of parentheses
-5x^2+5x-15x+15=0
We add all the numbers together, and all the variables
-5x^2-10x+15=0
a = -5; b = -10; c = +15;
Δ = b2-4ac
Δ = -102-4·(-5)·15
Δ = 400
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{400}=20$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-10)-20}{2*-5}=\frac{-10}{-10} =1 $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-10)+20}{2*-5}=\frac{30}{-10} =-3 $

See similar equations:

| a=9a^2+3 | | r+3=15 | | 144.4=2x | | c=24.50(3)+9.50 | | 7-5p-4p=-3p-5 | | x+5-6=-7 | | 0=6r-7r | | x-6-8=-19+x | | 2(3m+5)=22 | | 7p+-18p=11 | | x+5-6=7 | | 7(x+4)=5x-8 | | (6)-9=2x-6 | | -3(h+5)=-12 | | 4+2p=-(-5p+8) | | 12+b=15.7 | | 7=6+b/2 | | (x-6)+5=24 | | h7=-9 | | 5x+23=2(x–5) | | 2x-1=-(2x+8) | | 4x+2(3x-2)=46 | | -3(4x+3)+4(1+6x)=43 | | 6(h+4)=-2( | | -6+x/4=5- | | 8n−​(2n+5​)=7 | | 4y-9-2y+8=0 | | 2(6n+9)=6(n-10) | | 1.3-10x=-8.7 | | 3(p-10)=-18 | | -11=-x/2 | | 7w+19+2w=55 |

Equations solver categories